PENERAPAN AJARAN TRIKAYA PARISUDHA MELALUI PENDEKATAN HUMANISTIK - Kusuma I Made Wirahadi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
The role of cultural values as a form of local wisdom that is rooted in the teachings of Hindu religious literature, of course, should be revived to collaborate with a variety of learning paradigm that developed today in order to gradually reflected in shaping human decency. Tri Kaya Parisudha is one of the many forms of teaching began to be forgotten. Though the concept of Tri Kaya Parisudha is a form of local wisdom that comes from the Hindu doctrine that is full of meaning and value that can later be applied in life keluraga, meningat family is the first educational institution and the main yan. Tri Kaya Parisudha provide an emphasis on the importance of the establishment of the livelihood of the simplest to stick to the truth, namely thinking, berkatadan do the right thing, which starts from oneself. Tri Kaya Parisudha indicate a wide range of values that can be transformed to form a human morals. The essence of the teachings of Tri Kaya Parisudha covers three main topics, namely the purification of thoughts, words purification and sanctification by works. Thus the doctrine of Tri Kaya Parisudha is a form of wisdom Lokai very refresentatif raised as one alternative to improve the understanding of the teaching of ethics and deontology. Keyword: Tri Kaya Parisudha, Humanistic Approach Method